SOCIAL MOBILITY OF FAMILIES AT RISK - Vaitiekus, Edmundas; Šakalytė, Danguolė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Social mobility is shifting from one social status to another, commonly to a status that is either higher or lower. Disadvantaged family affects all social risk: poverty, unemployment, and addictions, violence, crime environment. The authors try to review the situation of families at risk in the community; to investigate the changes of social mobility of the families at risk. The aim of research in presented article is – to reveal the social mobility and the changes of the social status of families at risk in X community. Performing the research, the literature analysis and instantly qualitative study were done. Several qualitative research methods: observation, genogram, family social network, and family functioning assessment questionnaire were selected.